Absence of TRIM32 Leads to Reduced GABAergic Interneuron Generation and Autism-like Behaviors in Mice via Suppressing mTOR Signaling. (11th December 2019) - Zhu, Jian-Wei; Zou, Ming-Ming; Li, Yi-Fei; Chen, Wen-Jin; Liu, Ji-Chuan; Chen, Hong; Fang, Li-Pao; Zhang, Yan; Wang, Zhao-Tao; Chen, Ji-Bo; Huang, Wenhui; Li, Shen; et al.
Abstract: Mammalian target of rapamycin (mTOR) signaling plays essential roles in brain development. Hyperactive mTOR is an essential pathological mechanism in autism spectrum disorder (ASD). Here, we show that tripartite motif protein 32 (TRIM32), as a maintainer of mTOR activity through promoting the proteasomal degradation of G protein signaling protein 10 (RGS10), regulates the proliferation of medial/lateral ganglionic eminence (M/LGE) progenitors. Deficiency of TRIM32 results in an impaired generation of GABAergic interneurons and autism-like behaviors in mice, concomitant with an elevated autophagy, which can be rescued by treatment embryonically with 3BDO, an mTOR activator. Transplantation of M/LGE progenitors or treatment postnatally with clonazepam, an agonist of the GABAA receptor, rescues the hyperexcitability and the autistic behaviors of TRIM32 −/− mice, indicating a causal contribution of GABAergic disinhibition. Thus, the present study suggests a novel mechanism for ASD etiology in that TRIM32 deficiency-caused hypoactive mTOR, which is linked to an elevated autophagy, leads to autism-like behaviors via impairing generation of GABAergic interneurons. TRIM32 −/− mouse is a novel autism model mouse.